Method and adsorbent for adsorbing and separating Th (IV) from acidic aqueous solution

By combining nitrogen-containing soft ligand derivatives with macroporous resins into adsorbents, using its unique five-membered ring structure to coordinate with Th(IV), the problem of low adsorption efficiency in strong acidic aqueous solutions is solved, and high efficiency is achieved The separation and recycling of thorium are suitable for industrial applications.

CN119158550APending Publication Date: 2024-12-20ZHEJIANG CENT FOR DISEASE CONTROL & PREVENTION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411128031.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art has low adsorption efficiency of Th(IV) in strongly acidic aqueous solutions, especially under conditions of pH 2-3, which significantly reduces the adsorption effect, making it difficult to effectively separate and recover thorium resources.

Method used

The composite material of the nitrogen-containing soft ligand derivative R-POPhen and macroporous resin is used as the adsorbent. It forms a stable coordination with Th(IV) through a unique five-membered ring structure, and combines the mesoporous structure of macroporous resin to achieve high Thorium adsorption separation under acidity.

Benefits of technology

Maintaining an adsorption efficiency of more than 75% at an acid concentration of 4mol/L, it has high acidity and acid resistance to protonation, it has simple operation and high separation efficiency, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158550A_ABST
    Figure CN119158550A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of spent fuel post-treatment, and discloses a method for adsorbing and separating Th (IV) from an acidic aqueous solution and an adsorbent, a composite material of a nitrogen-containing soft ligand derivative R-POPhen and macroporous resin is used as the adsorbent, and the Th (IV) is adsorbed and separated from the acidic aqueous solution; the structure of R-POPhen is shown in the specification, the adsorbent is formed by compounding a nitrogen-containing ligand of phenanthroline phosphorus oxide and macroporous resin, adsorption separation of thorium can be achieved under high acidity, and the adsorption efficiency can still reach 75% or above under the acid concentration of 4 mol / L. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spent fuel post-processing, and in particular to a method and an adsorbent for adsorbing and separating Th(IV) from an acidic aqueous solution. Background Art

[0002] With the continuous increase in fossil energy consumption, the energy crisis has become the focus of global attention. Therefore, nuclear energy, as one of the clean energy sources, has received widespread attention. However, many defects in the use of nuclear energy still need to be overcome. As the current mainstream uranium-based light water reactor, the nuclear safety, nuclear waste disposal, fuel supply and other issues that come with its development and application have always been issues of great concern to the public. The fourth-generation nuclear power technology using thorium (Th) as nuclear fuel - thorium-based molten salt reactor can effectively solve the above problems. Thorium itself has lower radiation than uranium and is 100 times safer than uranium. The safety factor of thorium-based molten salt reactor is also very high. Fluoride salt as a coolant has no risk of high-temperature burning. Even if an accident occurs, there will basically be no nuclear leakage or environmental pollution. Thorium's utilization rate and energy conversion efficiency are better than uranium. Using the same weight of nuclear fuel, it can generate 250 times more energy than uranium-based technology. Thorium-based reactors produce very little radioactive waste. Using thorium as nuclear fuel can avoid the risk of nuclear weapons proliferation.

[0003] In addition, the reserves of thorium on Earth are far more abundant than uranium. The proven reserves in the earth's crust are currently three or four times that of uranium. With the application of thorium in high-tech fields such as vacuum and lighting industry, chemical industry, metallurgical industry and nuclear fuel application, the pollution problems brought about by it also need to be solved urgently. Since most of the radioactive wastewater containing Th(IV) is strongly acidic, and in a strongly acidic solution with a pH value of less than 2, almost all reported materials, including traditional TiO 2 ,γ-Al 2 O 3 , carbon nanotubes, and emerging metal-organic framework materials (MOFs), mesoporous carbon, covalent organic framework (COF) materials, etc. have very weak adsorption of Th(Ⅳ) or even lose the ability to adsorb and separate Th(Ⅳ).

[0004] For example, CN116550307A discloses a method for preparing a micro-membrane adsorption material for rapid and efficient adsorption of radioactive nuclide ions. A novel micro-membrane adsorption material based on zeolite imidazole framework-67 (ZIF-67) nanoparticles and polyamide microporous membrane (PA) was prepared by deep penetration method and in-situ synthesis method. The saturated adsorption capacity of Th(IV) in 50 min of the ZIF-67@PA micro-membrane adsorption material was 703.59 mg / g, and after being reused 7 times, it still had a super high adsorption capacity, indicating that the ZIF-67@PA micro-membrane adsorption material has excellent absorption capacity and reusability, showing great potential for industrial application. However, the best adsorption acidity condition is pH=5, and the adsorption effect is significantly reduced at pH 2-3.

[0005] CN112850955A discloses a method for removing uranium, thorium and thallium from wastewater. The method adds persulfate to the wastewater, mixes it evenly, then adds magnetic resin to react, adjusts the pH of the wastewater and leaves it to stand for treatment. The cheap and readily available strong oxidant sodium persulfate is used, and after activation by magnetic resin, strong oxidizing sulfate radicals and hydroxyl radicals are generated, which are much stronger than commonly used strong oxidants such as Cl 2 , ClO 2 , ClO - It has stronger oxidation ability and can decompose macromolecular organic matter into small molecular organic matter or mineralize it into CO 2 and H 2 In this method, NDMP magnetic resin is used, which, on the one hand, activates persulfate, and on the other hand, the resin itself is a strong alkaline anion resin that can adsorb coordinated anions such as uranium and thallium. The amount of reagent used is small and does not need to be added in large quantities. In addition, this method is relatively economical and has a high removal rate, with a removal rate of more than 99% for uranium and thorium and a removal rate of more than 98% for thallium.

[0006] However, this method requires the addition of a large amount of strong oxidant, and after adsorption, a large amount of alkali needs to be added to adjust the pH. The process is complicated and the amount of acid and alkali used is also high. Therefore, it is urgent to develop a suitable adsorbent with a simple preparation method, low cost and suitable for adsorbing and recovering thorium resources from strongly acidic aqueous solutions, and to efficiently separate Th(IV) from strongly acidic solutions. Summary of the invention

[0007] Aiming at the poor adsorption effect of thorium, especially the decrease or failure of the adsorption force of the adsorbent in a strong acid environment, the present invention provides a method for adsorbing and separating Th(IV) from an acidic aqueous solution. The adsorbent is composited with a nitrogen-containing ligand of o-phenanthroline phosphine oxide and a macroporous resin, and the adsorption and separation of thorium can be achieved under high acidity. At an acid concentration of 4 mol / L, the adsorption efficiency can still reach more than 75%.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for adsorbing and separating Th(IV) from an acidic aqueous solution comprises the following steps: using a composite material of a nitrogen-containing soft ligand derivative R-POPhen and a macroporous resin as an adsorbent to adsorb and separate Th(IV) from the acidic aqueous solution;

[0010] The structure of R-POPhen is as follows:

[0011]

[0012] Where R is

[0013] In the present invention, the O in the P=O double bond in the structure of o-phenanthroline phosphate is used as a coordinating atom, and together with the N in the o-phenanthroline skeleton, it can form a unique five-membered ring stable structure with +4-valent Th (IV), which provides a structural chemical theoretical basis for the efficient adsorption of thorium elements by this composite material. After combining this material with a macroporous resin, the macroporous structure contained in the macroporous resin can be fully utilized to improve the adsorption kinetics of the composite material, which is essentially different from the previous use of this type of ligand as an extractant based on the liquid-liquid solvent extraction method to extract and separate trivalent minor actinides and transuranium plutonium. And the study found that when it is under high nitric acid concentration, the nitrate contained in the nitric acid and Th (IV) can be directly complexed and coordinated, which makes the composite material invented by this patent have strong acid and protonation resistance characteristics.

[0014] In some embodiments, the macroporous resin is one or more of XAD-7, XAD-7, XAD-4, and XAD-2010. This type of macroporous resin is polymerized from methacrylic acid and has the advantages of rich mesoporous structure, large specific surface area, resistance to radiation decomposition, resistance to strong acid corrosion, and low cost.

[0015] In some embodiments, the mass ratio of R-POPhen to the macroporous resin is 1:1-5. As the loading amount of the compound R-POPhen increases, the capacity of the composite material for adsorbing thorium ions increases, but at the same time the stability and economy of the material decrease. Preferably, the mass ratio of R-POPhen to the macroporous resin is 1:2-3.

[0016] In some embodiments, the acid concentration in the acidic aqueous solution is 0.01-4 mol / L; the adsorbent in the present invention can have excellent thorium adsorption effect in a wide range of acidity.

[0017] In some embodiments, when R is When the acid concentration in the acidic aqueous solution is 0.1-4 mol / L; the butyl o-phenanthroline phosphate C4-POPhe, the Th(IV) adsorption rate is maintained above 70% in this acidity range; preferably, the acid concentration is 1.0-3.5 mol / L, and the Th(IV) adsorption rate is maintained above 80% in this acidity range; further preferably, the acid concentration is 2-3 mol / L, and the Th(IV) adsorption rate is maintained above 90% in this acidity range.

[0018] In some embodiments, when R is When the acid concentration in the acidic aqueous solution is 0.01-4 mol / L. Isobutyl o-phenanthroline phosphate iBu-POPhen has a stronger adsorption effect, and the Th(IV) adsorption rate is maintained at more than 80% in this acidity range; preferably, the acid concentration is 0.5-3.5 mol / L, and the Th(IV) adsorption rate is maintained at more than 90% in this acidity range.

[0019] Preferably, the acid is nitric acid.

[0020] In some embodiments, the mass volume concentration of the adsorbent in the acidic aqueous solution is 0.2 mg / mL or more, and in some embodiments, the mass volume concentration of the adsorbent is 0.2-2 mg / mL. Further, the amount of the adsorbent is 0.4-2 mg / mL, and the Th(IV) adsorption rate is 70% or more. When the adsorbent is 0.5 mg / mL or more, the Th(IV) adsorption rate is 90% or more.

[0021] In some embodiments, the adsorption time of the adsorbent is more than 30 seconds, preferably 1 minute to 6 hours. The adsorbent in the present invention has a very fast adsorption speed, and can reach an adsorption rate of nearly 70% within an adsorption time of more than 1 minute, and can achieve a Th(IV) adsorption rate of more than 80% within 10 minutes, and can basically reach an adsorption rate of 90% within about 4 hours.

[0022] In some embodiments, the temperature of the acidic aqueous solution during adsorption is 15°C-45°C.

[0023] In some embodiments, the acidic aqueous solution contains alkali metal, alkaline earth metal, transition metal or rare earth element impurities, and the total molar concentration of the impurity metal ions is less than 1000 times the molar concentration of Th(IV) ions.

[0024] In some embodiments, the impurity metal ions include one or more of alkali metals such as Na, K, Rb, Cs, alkaline earth metals such as Ca, Mg, Sr, Ba, rare earth elements such as La, Eu, Lu, and transition metals such as Fe, Ni, Cu, etc.

[0025] The present invention also provides an adsorbent for adsorbing and separating Th(IV), wherein the adsorbent is a composite material of a nitrogen-containing soft ligand derivative R-POPhen and a macroporous resin having the following structure:

[0026] The structure of R-POPhen is as follows:

[0027]

[0028] Where R is

[0029] The present invention also provides a preparation method of an adsorbent for adsorbing and separating Th(IV), comprising: mixing R-POPhen and a macroporous resin in a solvent, and vacuum drying to remove the solvent to obtain the adsorbent.

[0030] The solvent includes one or more of dichloromethane and methanol.

[0031] The mixing process is preferably carried out at 0-40°C, and physical vacuum infusion is performed under vacuum and stirring conditions.

[0032] The present invention also provides a nitrogen-containing soft ligand derivative, the structure of the nitrogen-containing soft ligand derivative is as follows:

[0033]

[0034] The present invention also provides a method for preparing the nitrogen-containing soft ligand derivative, comprising the steps of: subjecting 2,9-dichloro-1,10-phenanthroline and diisobutyl phosphite to a substitution reaction under catalysis to obtain the nitrogen-containing soft ligand derivative iBu-POPhen.

[0035] Preferably, the molar ratio of 2,9-dichloro-1,10-phenanthroline to diisobutyl phosphite is 1:2-3; the catalyst is a palladium catalyst, an acid binding agent is also included in the reaction process, the reaction is carried out under an inert gas, and the reaction is carried out at 100-120° C. for 7-10 hours.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The invention aims at solving the problems of low Th(IV) adsorption efficiency and low adsorption rate under high acidity in the prior art, and provides a macroporous resin composite material for adsorbing and separating radioactive nuclide thorium from a strongly acidic aqueous solution. The preparation method of the macroporous resin composite material is simple, the raw material cost is low, and it is easy to industrialize production. The obtained adsorption material has the advantages of effective adsorption of Th(IV) under high acidity, and the amount of adsorbent used is small, and the adsorption can be completed in a short time. When the adsorbent is used to separate Th(IV), the operation is simple and the separation efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the NMR spectrum of C4-POPhen prepared in Example 1.

[0039] Figure 2 This is the NMR spectrum of iBu-POPhen prepared in Example 1.

[0040] Figure 3 This is a diagram showing the adsorption effect of two adsorbents on Th(IV) at different acidities in Example 3.

[0041] Figure 4 This is a diagram showing the adsorption effect of two adsorbents on Th(IV) at different adsorbent dosages in Example 4.

[0042] Figure 5 This is a diagram showing the adsorption effect of two adsorbents on Th(IV) at different adsorption times in Example 5. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0044] The raw materials used in the following specific embodiments are all purchased from the market.

[0045] Example 1

[0046] The ligand C4-POPhen was prepared according to the preparation method of Example 2 of CN1111434785A. The NMR characterization results are as follows: Figure 1 shown.

[0047] The synthesis technology route of the ligand iBu-POPhen is as follows: accurately weigh 2.0g (8.0mmol) 2,9-dichloro-1,10-phenanthroline, 3.9g (20.0mmol) diisobutyl phosphite, 91mg (0.4mmol) catalyst palladium acetate and 445mg (0.8mmol) DPPF and place them in a 125mL three-necked flask, add a magnetic particle, and then use Schlenk technology to exhaust the air and fill with high-purity argon. Then, under an argon atmosphere, inject 80.0mL ultra-dry toluene and 1.5mL triethylamine through a syringe, turn on magnetic stirring and heat to 110℃ for stirring and reflux reaction for 7-10h. During the reaction, TLC thin-layer chromatography analysis is used to track the reaction to determine that the 2,9-dichloro-1,10-phenanthroline raw material is consumed. After the reaction, the mixture was cooled to room temperature and the solid impurities were removed by filtration. The reaction solvent was removed by rotary evaporator, and then column chromatography was used with dichloromethane / ethyl acetate / methanol (volume ratio of 30:30:1) as eluent for separation and purification to obtain 2.0 g of gray solid with a yield of 44%.

[0048] The NMR characterization results are as follows Figure 2 As shown: 1 H NMR (500 MHz, CDCl 3 )δin ppm:0.94ppm(t,24H,-CH 3 ),1.98ppm(m,4H,-CH-),4.06ppm(m,8H,-CH-) 2 -), 8.05ppm(s,2H,-Ar-H),8.24ppm(dd,2H,-Ar-H),8.54ppm(dd,2H,-Ar-H). Its theoretical molecular weight is: 564.2518 564. The high resolution molecular weight is: HRMS: m / z: [M+H] + =565.2587,[M+Na] + =587.2410.

[0049] Example 2

[0050] Activation method of XAD-7 carrier: There are residual solvents and fine impurities in the pores and on the surface of the purchased XAD-7 particles, which will affect the performance of the composite material. Therefore, it is necessary to pre-clean it with a cleaning solvent, dichloromethane, for multiple times. This is the activation treatment of XAD-7. The specific operation is as follows: weigh 20g of XAD-7 on an electronic balance, add 40mL of dichloromethane, stir with a magnetic stirrer at room temperature for 8h, remove dichloromethane by vacuum filtration, add 40mL of new dichloromethane and continue magnetic stirring, repeat 3 times, and vacuum dry at 75°C for 3h to obtain a pure white activated XAD-7 solid powder, which is stored in a vacuum dryer for later use.

[0051] The ligands C4-POPhen and iBu-POPhen prepared in Example 1 were weighed 0.5g respectively and placed in a 50mL single-necked flask, and 1.5g of activated XAD-7 and 30mL of dichloromethane solution were added in a mass ratio of 1:3 and mixed evenly at room temperature. Then the solvent was removed at 45°C under vacuum conditions. As the solvent was slowly removed, the o-phenanthroline ligand molecules were infused and fixed in the pores of the XAD-7 particles through capillary action and intermolecular interactions, and then dried at 60°C to obtain two composite adsorption materials iBu-POPhen / XAD-7 and C4-POPhen / XAD-7, respectively.

[0052] Example 3

[0053] The metal salt KNO 3 、Ca(NO 3 ) 2 、Eu(NO 3 ) 2 and Th(NO 3 ) 4 Dissolve in water to prepare an aqueous solution, the concentration of the above metal salts in the aqueous solution is 5.0×10 -5 mol / L. Add nitric acid to adjust the HNO 3 When the concentrations were 0.01 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, and 4 mol / L, 5.0 mL of the obtained aqueous solutions with different nitric acid concentrations were respectively placed in a 15 mL culture bottle for contact and mixing with 10.0 mg of the composite material of Example 2, and then adsorption and shaking were carried out on a TAITECMM-10 shaker with an shaking rate of 120 rpm, a temperature of 25°C, and a shaking time of 240 min to allow the adsorption to reach equilibrium, and then the contents of each element in the different nitric acid aqueous phases before and after adsorption were measured.

[0054] The separation results are as follows Figure 3 As shown in Table 1, it can be seen that when the pH of the nitric acid solution is less than 2, the adsorption efficiency of C4-POPhen / XAD-7 is above 80%. When the concentration of the nitric acid solution is 2 mol / L, the effect of separating Th(Ⅳ) is the best, and the adsorption efficiencies of iBu-POPhen / XAD-7 and C4-POPhen / XAD-7 are 92.48% and 97.59%, respectively.

[0055] Table 1 Experimental results of Th(Ⅳ) adsorption on composite materials

[0056]

[0057] Example 4

[0058] According to the process steps of Example 3, the nitric acid concentration was fixed at 2.0 M, the temperature was 25 ° C, and the time was 240 min. When the amount of adsorbent was changed, the amount of adsorbent was 0.1 mg / mL, 0.2 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 1.0 mg / mL, and 2.0 mg / mL, respectively. The adsorption results are as follows: Figure 4 As shown in Table 2. It can be seen that the adsorption efficiency increases with the increase of adsorbent dosage. When the adsorbent concentration is greater than 0.5 mg / mL, the adsorption efficiency of iBu-POPhen / XAD-7 reaches 92.4%; when the adsorbent concentration is greater than 0.4 mg / mL, the adsorption efficiency of C4-POPhen / XAD-7 is greater than 91.40%; when the adsorbent concentration is 2.0 mg / mL, both iBu-POPhen / XAD-7 and C4-POPhen / XAD-7 can basically completely remove Th(Ⅳ), and the adsorption efficiencies are 99.03% and 99.51%, respectively.

[0059] Table 2 Experimental results of Th(Ⅳ) adsorption by different amounts of composite materials

[0060]

[0061] Example 5

[0062] According to the process steps of Example 3, the nitric acid concentration was fixed at 3.0 M, the adsorbent concentration was fixed at 1.0 mg / mL, the temperature was 25°C, and only the contact time between the adsorbent and the acidic aqueous solution to be treated was changed. The adsorption results are as follows: Figure 5 And as shown in Table 3.

[0063] It can be seen that with the increase of contact time, the adsorption efficiency first increases. After C4-POPhen / XAD-7 reaches 91.21% at 60min, the growth rate gradually slows down and reaches 94.43% at 240min, and then fluctuates in a small range, indicating that the adsorption of Th(Ⅳ) by C4-POPhen / XAD-7 composite material can reach adsorption equilibrium at 240min. The adsorption efficiency of iBu-POPhen / XAD-7 reaches 83.94% after 10min, and then slowly increases to 90.4% at 240min.

[0064] Table 3 Experimental results of Th(Ⅳ) adsorption on composite materials at different adsorption times

[0065]

[0066]

Claims

1. A method for separating Th(IV) by adsorption from an acidic aqueous solution, characterized in that: The method comprises the following steps: using a composite material of a nitrogen-containing soft ligand derivative R-POPhen and a macroporous resin as an adsorbent to adsorb and separate Th(IV) from an acidic aqueous solution; The structure of R-POPhen is as follows: Where R is 2. The method for adsorbing and separating TH(IV) from an acidic aqueous solution according to claim 1, characterized in that: The macroporous resin is one or more of XAD-7, XAD-4, and XAD-2010; And / or, wherein the mass ratio of R-POPhen to the macroporous resin is 1:1-1:

5.

3. The method for adsorbing and separating TH(IV) from an acidic aqueous solution according to claim 1, characterized in that: The acid concentration in the acidic aqueous solution is 0.01-4 mol / L; Preferably, when R is When the acid concentration in the acidic aqueous solution is 0.1-4 mol / L; When R is When the acid concentration in the acidic aqueous solution is 0.1-4 mol / L.

4. The method for adsorbing and separating TH(IV) from an acidic aqueous solution according to claim 1, characterized in that: The mass volume concentration of the adsorbent in the acidic aqueous solution is above 0.2 mg / mL, and preferably the mass volume concentration of the adsorbent is 0.2-2 mg / mL.

5. The method for adsorbing and separating TH(IV) from an acidic aqueous solution according to claim 1, characterized in that: The adsorption time of the adsorbent is more than 30 seconds, and the preferred adsorption time is 1 minute to 6 hours.

6. The method for adsorbing and separating TH(IV) from an acidic aqueous solution according to claim 1, characterized in that: The temperature of the acidic aqueous solution during adsorption is 15°C-45°C; And / or, the acidic aqueous solution contains alkali metal, alkaline earth metal, transition metal or rare earth element impurities, and the total molar concentration of the impurity metal ions is less than 1000 times the molar concentration of Th(IV) ions.

7. An adsorbent for adsorbing and separating Th(IV), characterized in that: The adsorbent is a composite material of a nitrogen-containing soft ligand derivative R-POPhen and a macroporous resin having the following structure; The structure of R-POPhen is as follows: Where R is 8. The method for preparing an adsorbent for adsorption and separation of Th(IV) according to claim 7, characterized in that: include: After R-POPhen and the macroporous resin are mixed in a solvent, the solvent is removed by vacuum drying to obtain the adsorbent.

9. A nitrogen-containing soft ligand derivative, characterized in that: The structure of the nitrogen-containing soft ligand derivative is as follows:

10. The method for preparing the nitrogen-containing soft ligand derivative according to claim 9, characterized in that: The method comprises the steps of: subjecting 2,9-dichloro-1,10-phenanthroline and diisobutyl phosphite to a substitution reaction under catalysis to obtain the nitrogen-containing soft ligand derivative.

Citation Information

Patent Citations

  • Method for removing uranium, thorium and thallium in wastewater

    CN112850955A

  • Preparation method of micro-membrane adsorption material for rapidly and efficiently adsorbing radionuclide thorium ions

    CN116550307A